2022
DOI: 10.3390/cryst12020191
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed GaN-Based Superluminescent Diode for 4.57 Gbps Visible Light Communication

Abstract: Visible light communication (VLC) is a promising technology for next-generation high-speed optical wireless data links. Among various transmitters, GaN-based superluminescent diodes (SLDs) show interesting characteristics, including a large modulation bandwidth, droop free and low speckle noise, which makes them attractive for VLC applications. In this work, we design and fabricate a blue-emitting SLD utilizing tilted facet configuration. Using SLD as the light source, a VLC system is experimentally demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A net data rate of 6.48 Gb/s at a bit error ratio (BER) of 3.6 × 10 −3 was achieved, which meets the 7 %-overhead forward error correction (FEC) BER limit of 3.8 × 10 −3 . It should be noted that this link demonstrated a 50% improvement over the previous record using SLDs 12 (4.6 Gb/s) even with this 3-m-long transmission distance.…”
Section: Resultsmentioning
confidence: 59%
“…A net data rate of 6.48 Gb/s at a bit error ratio (BER) of 3.6 × 10 −3 was achieved, which meets the 7 %-overhead forward error correction (FEC) BER limit of 3.8 × 10 −3 . It should be noted that this link demonstrated a 50% improvement over the previous record using SLDs 12 (4.6 Gb/s) even with this 3-m-long transmission distance.…”
Section: Resultsmentioning
confidence: 59%
“…Notable research efforts have explored the use of low-coherence light sources for data transmission across various scenarios 61,191,192 . In 2016, Shen et al, investigated for the first time the implementation of low coherent light using semipolar GaN SLDs in communication systems 61 .…”
Section: Optical Communication and Illuminationmentioning
confidence: 99%
“…Shen et al demonstrated the generation of white light using an SLD with a high color rendering index (CRI) of 88.2 at a correlated color temperature (CCT) of 3522 K, and it was used in a VLC system with a high data rate of 1.2 Gb s -1 using the OOK modulation technique and up to 3.4 Gb s -1 using the discrete multitone (DMT) modulation technique 53 . More recently, the highest communication data rate using an SLD was demonstrated (up to 4.6 Gb s -1 using DMT) 192 . The application of SLDs in communication systems has yielded promising results and has the potential to revolutionize high-speed data transmission, offering a balance between power, safety, and efficiency.…”
Section: Optical Communication and Illuminationmentioning
confidence: 99%
“…[ 16 ] A blue SLD with a wavelength of 443 nm, using DMT modulation, can reach a data rate of 4.57 Gbps, currently the highest data rate achieved by SLD. [ 19 ] However, it is worth noting that excessive exposure to blue light may have negative effects on health, as it inhibits the production of melatonin in the human body. Consequently, research on SLDs in the violet spectrum range is relatively lacking.…”
Section: Introductionmentioning
confidence: 99%